GUI Development for Economic Dispatch Analysis on Sulselrabar Power Plant - Hamzah, Nur; Djalal, Muhammad Ruswandi; Musa, La Ode; Buana, Chandra (Politeknik Negeri Ujung Pandang, 2022)
The take or pay contract between PT. PLN (Persero) with Independent Power Producer (IPP), a power plant belongs to PT. PLN (Persero) is no longer operated optimally, for example, the Barru steam power plant. The steam power plant is a power plant that bears the primary load. The actual conditions in the Barru steam power plant field are charged a maximum of only 3-4 hours or only when the peak load is according to the dispatcher's request. This research examines comparing the economy dispatch method to maximize conditions in the Barru steam power plant, which dispatchers no longer order maximally. So that the Barru power plant operator can determine the distribution of the power allocation ordered by the dispatcher to the two power plant units of the Barru steam power plant, the method being compared is the lambda iteration method. The basis for calculating the two ways is to calculate in advance the characteristics of the fuel consumption of the power plant when operating in one day. The primary data is data on the results of electricity production issued by the generator and fuel consumption taken from the coal feeder flow. Based on the research results, it is known that the lambda iteration method can save production costs of Rp. 9.05 per KWH.